Achieving High Voltage and Excellent Rate Capability Supercapacitor Electrodes Derived From Bio‐renewable and Sustainable Resource. Issue 28 (30th July 2020) - Vijayakumar, Manavalan; Bharathi Sankar, Ammaiyappan; Sri Rohita, Duggirala; Nanaji, Katchala; Narasinga Rao, Tata; Karthik, Mani
Abstract: The design and development of bio‐renewable and sustainable carbon‐carbon based supercapacitor electrodes provide high volumetric energy density and high durability even at higher potential window are one of the major technological challenges. The present study demonstrates the conversion of wheat flour as bio‐renewable and sustainable resource into hierarchical high surface area bi‐model porous carbon nanosheets (1620 m 2  g −1 ) as high performance supercapacitor electrode. Bi‐model porous carbon can provide the high electrochemical performance because it has optimum textural characteristic. The benefit from simultaneous achievement of extended voltage window of 3.2 V and high volumetric capacitance of 86 F cm −3 with high electrode density of 0.76 g cm −3, the supercapacitor cell can provide higher volumetric energy density of 30.46 Wh L −1 . Particularly, supercapacitor cell shows exceptional rate capability at commercial level active mass loading (10 mg cm −2 ) and high durability at 3.2 V upon 15, 000 charge‐discharge cycles with 95 % of capacitance retention. The integrated power electronic booster and the concept of recovery of the stored energy from the supercapacitor are explained by a simulation as well as experimental study for the first time. This work inspires new insights to develop a sustainable high volumetric supercapacitor for portable and wearable device applications. Abstract : High surface area porous carbon was prepared from wheat flour as biorenewable and sustainable carbon feedstock for high volumetric energy density supercapacitor. The recovery of stored energy from the supercapacitor device with the help of integrated electronic booster circuit was successfully demonstrated by using LED torch light for practical validity.